2016
DOI: 10.1007/s12325-015-0276-3
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Subcutaneous Methotrexate in Rheumatoid Arthritis Patients After Failure or Intolerance to Oral Methotrexate: A Multicenter Cohort Study

Abstract: IntroductionLow-dose weekly methotrexate (MTX) is the mainstay in the therapy of rheumatoid arthritis (RA). It can be given via oral, intramuscular or subcutaneous (SC) route. This study sought to determine the real-world pattern of treatment with SC MTX in Portuguese adult patients with active RA.MethodsUtilization of Metoject® in Rheumatoid Arthritis (UMAR) was a non-interventional, cohort multicenter study with retrospective data collection. Eligible patients had active RA, at least 18 years of age, and sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…For each study, data were extracted and quality was assessed. Results are summarized in Table 1 9,11,12,19,20,21,22,23,24,25,26,27 , Table 2, Table 3 [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47]48,49,50,51,52,53,54,55,56 , and Table 4, as well as Supplementary Table 2 and Supplementary Table 3 (available online at jrheum.org). MTX adherence.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For each study, data were extracted and quality was assessed. Results are summarized in Table 1 9,11,12,19,20,21,22,23,24,25,26,27 , Table 2, Table 3 [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47]48,49,50,51,52,53,54,55,56 , and Table 4, as well as Supplementary Table 2 and Supplementary Table 3 (available online at jrheum.org). MTX adherence.…”
Section: Resultsmentioning
confidence: 99%
“…Persistence with MTX. Twenty-nine studies evaluated persistence with MTX (Table 3) [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47]48,49,50,51,52,53,54,55,56 . Most were in the United States and Europe, and 1 each in Israel, India, and Japan.…”
Section: Rheumatologymentioning
confidence: 99%
“…It has been reported that subcutaneous use of MTX provides excellent tolerability and compliance with equivalent efficacy to oral treatment. 13 …”
Section: Discussionmentioning
confidence: 99%
“…A synopsis of the most relevant tolerability outcomes observed in clinical studies involving patients with RA and JIA is shown in Table 4 . 27 31 , 33 , 35 , 38 – 45…”
Section: Introductionmentioning
confidence: 99%
“…Some retrospective studies have documented relatively high persistence rates of SC MTX treatment, 33 , 38 and this, therefore, may minimize or postpone the need to initiate expensive biological therapy. However, there are controversial data from the real-life experience.…”
Section: Introductionmentioning
confidence: 99%